Power Islamization: Unveiling the Islamic Politics of Kiai as Leaders of The Indonesian People - Azharghany , Rojabi (LPPPM STAI Darul Hikmah Bangkalan, 2022)
This research aims to review the Islamic politics of the Kiai affiliated with the religious organization called Nahdlatul Ulama (NU) examining the Kiai's Islamic politics focusing on the social-historical arguments and strategies promoted by the religious elites to keep their role in the lives of Muslims. Within the political dynamics of modern Islamic lifestyle, Kiai still holds their position as honorable figures. The methodology of this study uses the social history school as a research method to see the social background in the Islamic political history of the kiai as well as contains a critical aspect to analyze the dynamics of the kiai's Islamic politics. This study is carried out by reconstructing socio-political events involving traditionalist kiai on the Indonesian political stage from the independence period until the 2019 election. The main finding in this study is that the Islamic politics promoted by the Kiai are based on the Islamic teachings about social concern such as maslahah mursalah and kulliatul khoms which created the Kiai's movement concept, namely mabadi’ khoiru ummah (a path that shapes the best people) and syuun ijtimaiyah (social concern). The Kiai’s involvement in politics is based on this foundation. The significance of this study takes social history as a method by introducing a new approach in revealing the political and socio-cultural significance of the kiai in his involvement in the power-politics arena in Indonesia. So that it can fully demonstrate the values built by the kiai towards Muslims in political education that leads to building awareness of the nation and state.